Polymethylmethacrylate a flexible membrane for a tailored dialysis - Ronco, Claudio 1951- (Contributions to nephrology, 1999)
This book surveys experiences made with Polymethylmethacrylate (PMMA) dialysis membranes, ranging from a summary of the most recent experimental and clinical results to an overview of future potentials and new trends in research. Several articles treat the biophysical properties of the membrane, its chemical structure and manufacturing procedures aimed at obtaining hollow fibers suitable for medical purposes. Moreover, various experimental conditions are considered in order to identify the dialytic properties of the PMMA membrane and dialyzer series. In this context, particular emphasis is put on the last generation of PMMA membranes with higher porosity and ultrafiltration capacity. On the more practical side, an overview is given of various clinical conditions in which PMMA membranes are utilized at variable rates of ultrafiltration, blood and dialysate flows. The bio- or hemocompatibility of PMMA membranes is investigated, offering a summary of the blood-membrane interactions during hemodialysis. Furthermore, the importance of these aspects in relation to the chronic dialyzed and the acutely ill patients is highlighted, as well as long-term experiences made with different PMMA membranes. For those interested in the last developments and clinical results achieved with synthetic membranes, this book provides a substantial piece of information valuable either for further research or daily clinical practice